2021
DOI: 10.14202/vetworld.2021.1874-1878
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in acid-base balance, blood gases, and hematobiochemical profiles of whole-blood and thoracic fluid in goats with contagious caprine pleuropneumonia

Abstract: Background and Aim: Contagious caprine pleuropneumonia (CCPP) is a highly contagious and fatal disease affecting goats and some wild ruminants. It is a cause of major economic losses in the goat industry in Africa, Asia, and the Middle East. This study aimed to investigate the acid-base balance, blood gases, and hematobiochemical profiles of whole-blood and fluid collected from the thoracic cavity in goats with CCPP. Materials and Methods: Fifty-five goats suffering from weight loss, anorexia, dyspnea, polypn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Differential diagnoses included abscessation, neoplasia or hemorrhage. A free-hand, ultrasound-guided technique was used in several studies for aspiration and biopsy of pathologic lesions as we reported previously Tharwat et al 2018a,b,c;Tharwat 2021;Tharwat et al 2023). Similar, the technique was helpful in current study to get a transcutaneous needle aspirate for bacteriologic evaluation and also facilitated intra-lesional antibiotic administration and drainage as the thick lesion capsule hinders the antibiotic diffusion.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Differential diagnoses included abscessation, neoplasia or hemorrhage. A free-hand, ultrasound-guided technique was used in several studies for aspiration and biopsy of pathologic lesions as we reported previously Tharwat et al 2018a,b,c;Tharwat 2021;Tharwat et al 2023). Similar, the technique was helpful in current study to get a transcutaneous needle aspirate for bacteriologic evaluation and also facilitated intra-lesional antibiotic administration and drainage as the thick lesion capsule hinders the antibiotic diffusion.…”
Section: Discussionmentioning
confidence: 63%
“…Complications associated with the ultrasound-guided percutaneous aspiration of the abscess in the present case were not encountered. The same approach of ultrasound-guided free-hand aspiration and biopsy methodology was also reported to be helpful for getting pathological aspirate and specimens (Mohamed et al 2003a,b,c,d;Mohamed et al 2004;Mohamed and Oikawa 2008;Tharwat et al 2018a,b,c;Tharwat 2021;Tharwat et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Blood PCO 2 , PO 2 , BE, HCO 3 , TCO 2 , and SO 2 have been found low in CCPP affected goats whereas AnGap has been found higher (Tharwat 2021). Further metabolic acidosis has been noted in CCPP affected goats (Tharwat 2021).…”
Section: Common Diagnostic Tests For Ccppmentioning
confidence: 87%
“…Hypoproteinaemia, rise in liver enzymes, calcium and glucose have been reported in mycoplasma affected goats (Mondal et al 2004). Changes in acid-base balance, blood gases, and hematobiochemical profiles in blood and thoracic fluid of CCPP affected goats has been evaluated (Tharwat 2021). Blood PCO 2 , PO 2 , BE, HCO 3 , TCO 2 , and SO 2 have been found low in CCPP affected goats whereas AnGap has been found higher (Tharwat 2021).…”
Section: Common Diagnostic Tests For Ccppmentioning
confidence: 99%
See 1 more Smart Citation